Health and socioeconomic circumstances over three generations as predictors of youth unemployment trajectories - David Teye Doku; Paulyn Jean Acacio-Claro; Leena Koivusilta; Arja Rimpelä (Oxford University Press, 2022)
Background
Youth unemployment is a critical life event, which may trigger other labour market-related disadvantages and detrimental health implications. To better understand the processes causing unemployment, we study how socioeconomic circumstances of successive generations and familial and health factors in adolescence predict youth unemployment trajectories between ages 16 and 28 in Finland from 2000 to 2009.
Methods
We used survey data from 1979 to 1997 on 12- to 18-year-old Finns (n = 43 238) linked with 1970–2009 registry-based data of their grandparents, parents and themselves. Growth mixture modelling and multivariate logistic regression analyses were used.
Results
Three latent youth unemployment trajectories emerged; low (46%), decreasing (38%) and high (16%) risk groups. Of adolescent factors, low school achievement was the most important predictor of youth unemployment followed by smoking, stress symptoms and poor self-rated health. Grandparents’ education predicted their grandchildren’s unemployment but the effects of other grandparental socioeconomic circumstances mediated through parents’ socioeconomic status (SES). Parents’ low SES and education, and long-term unemployment increased the risk of the child’s unemployment. Youth unemployment was related to low education at the age of 29.
Conclusion
Grandparents’ education, family socioeconomic circumstances and adolescents’ health and school achievement predict the developmental trajectory of youth unemployment. Youth unemployment is also related to low education in early adulthood. Our findings suggest that the health selection of unemployment works already in adolescence.